TOURISM AS A DRIVING FORCE IN RURAL DEVELOPMENT: THE CASE STUDY OF SOUTHEASTERN BAČKA - Pavlović, Nataša; Kovačević Berleković, Bojana M (International Journal of Economic Practice and Policy, 2019)
The goal of the study is to research the current state and the potential for development of tourism in Southeastern Bačka, defining the target segment of the market, as well as proposals for creating a tourism product and including the local community in an integrated development of tourism. Primary research for the study included electronic surveys conducted in Novi Sad and Zrenjanin, based on a sample of 322 respondents. It was essential to determine the target markets that can generate most visitors and tourists, followed by establishing which target market segment the marketing activities should be primarily focused on. The main goal of this research was to establish the steps that would contribute to activating recreational spaces and protected natural areas of Southeastern Bačka for tourism purposes.